2012
DOI: 10.1007/s12031-012-9875-5
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TREK-1 Activity in Astrocyte Function and Neuroprotection Under Simulated Ischemia Conditions

Abstract: Astrocytes play a fundamental role in the pathogenesis of ischemic neuronal death. The optimal operation of electrogenic astrocytic transporters and exchangers for some well-defined astrocyte brain homeostatic functions depends on the presence of K(+) channels in the cell membranes and the hyperpolarized membrane potential. Our previous study showed that astrocytes functionally express two-pore domain K(+) channel TREK-1, which helps to set the negative resting membrane potential. However, the roles of TREK-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…However, in brains 5W after ischemia we found many reactive astrocytes with significantly depolarized RMP and decreased R M . These altered properties suggest changes in the composition of cytoplasmic membrane channels, such as Kir4.1 or two-pore domain K 1 channels as shown previously (Kucheryavykh et al, 2009;Pivonkova et al, 2010;Wu et al, 2013). The recorded inward currents, sensitive to HCN channel blocker and co-agonist, together with the demonstrated Na 1 conductance, imply that the HCN channels are one of the main players in the altered membrane properties of reactive astrocytes.…”
Section: Discussionsupporting
confidence: 75%
“…However, in brains 5W after ischemia we found many reactive astrocytes with significantly depolarized RMP and decreased R M . These altered properties suggest changes in the composition of cytoplasmic membrane channels, such as Kir4.1 or two-pore domain K 1 channels as shown previously (Kucheryavykh et al, 2009;Pivonkova et al, 2010;Wu et al, 2013). The recorded inward currents, sensitive to HCN channel blocker and co-agonist, together with the demonstrated Na 1 conductance, imply that the HCN channels are one of the main players in the altered membrane properties of reactive astrocytes.…”
Section: Discussionsupporting
confidence: 75%
“…TREK1 protein expression was temporally increased in these cells at 6 h after hypoxia. However, blockade of TREK1 channels raised the number of hypoxia-induced neuronal apoptosis in a neuron-astrocyte co-culture indicating a neuroprotective role of TREK1 channels after hypoxia [41]. In line with that, former studies on K 2P channels in stroke also revealed that TASK1 and TREK1 are involved in neuroprotection after stroke in mice while a closely related channel (TASK3) had no influence.…”
Section: Discussionmentioning
confidence: 70%
“…Recent studies have suggested unexpected roles for TREK-1 in glutamate conductance (Hwang et al, 2014; Woo et al, 2012) and regulation of blood–brain barrier permeability (Bittner et al, 2013). Channel activity has been linked to several pathological conditions, such as cardiac hypertrophy (Wang et al, 2013), ischemia (Heurteaux et al, 2004; Laigle, Confort-Gouny, Le Fur, Cozzone, & Viola, 2012; Wu et al, 2013), and myocardial infarction (Zhao, Fu, Gao, Xie, & Cao, 2011). …”
Section: Introductionmentioning
confidence: 99%